Heterogeneity analysis of extracellular vesicles from four edible crops: structural characteristics and functional evaluation - Shuhong Li; Kefan Guo; Yuning Song; Shaoting Yuan; Guiyun Chen; Ye Chen (Food Chemistry, 2026)

A dual-enhanced magnetically separable SERS strategy enabled by Fe3O4@Au nanovilli and UiO-66-NH2 for ultrasensitive detection of p-tau217 - Junyu Chen; Yichuan Liang; Panqing Xu; Chenyao Kong; Yuting Zhang; Ruyang Zhou; Ouyingmei Wu; Zeng Jiang; Haonan Zhao; Mingrui Song; Tao Jiang; Yuning Pan (Analytica Chimica Acta, 2026)

Food-derived extracellular vesicles: an emerging intervention strategy for inflammatory bowel disease - Yimeng Wang; Yuning Zhang; Sijia Song; Juan Chen; Huiyuan Guo; Yingying Lin (Critical Reviews in Food Science and Nutrition, 2026)

Mangrove-inspired salt-excreting evaporator for enhanced solar desalination and mineral salt harvesting - Dengkai Xu; Jin Yang; Lixuan Zhao; Xiayuan Zhang; Yuning Liu; Xiaohua Jia; Haojie Song (Desalination, 2026)

Identification of the geographical origin of wild rice field eel (Monopterus albus) in China by stable isotopes - Weiwei Lv; Muyan Li; Yangyang Lu; Yifan Zhao; Weiwei Huang; Hang Yang; Quan Yuan; Yuning Zhang; Mingyou Li; Wei Hu; Chunxia Yao; Danhe Wang; et al. (Food Control, 2026)

Study on Material Parameter Value Method and Numerical Simulation of Spherical Tooth Impact Rock Breaking Model - Yi Cao; Yansen Wang; Guoxuan Song; Yuning Wang; Zhihao Hou (Rock Mechanics and Rock Engineering, 2025)

Automated evaluation of dairy goat body condition and analysis of differences in lumbar features, milk composition and blood biochemical indicators - Yuning An; Yifeng Song; Ziqi Meng; Yuan Wang; Buyu Wang; Na Liu; Jingwei Qi; Ming Xu; Xiaoping An (Small Ruminant Research, 2025)

Insight into homogeneous activation of sodium hypochlorite by dithionite coupled with dissolved oxygen (DO@NaClO/DTN) for carbamazepine degradation - Wei Song; Hongze Fang; Zhaosheng Lei; Ruigang Wang; Caixia Fu; Fei Wang; Yuning Fang; Xing Du; Zhihong Wang; Zhiwei Zhao (Water Research, 2025)

OH-isoGDGTs as a paleothermometer for bottom seawater temperature in the eastern China marginal seas - Yuning Wang; Huamao Yuan; Jinming Song; Junhui Chen; Fengmin Pan; Qidong Wang; Xuegang Li; Liqin Duan; Ning Li; Yueqi Wang (Chemical Geology, 2025)

PEI-SiO2/GO nanofiltration membrane: Achieved high water permeability and dye rejection rate - Kexin Tao; Yuning Zhang; Yu Song; Zhiyuan Chen; Yao Wang; Yanxin Wang; Jianguo Tang; Linjun Huang (Journal of Environmental Chemical Engineering, 2025)

Dissolved oxygen activated by single-atom-state iron coupled with sodium dithionite for norfloxacin degradation: Efficiency and mechanism - Wei Song; Sen Xu; Caixia Fu; Ruiyi Huang; Hongze Fang; Li Li; Dachao Lin; Yuning Fang; Xing Du; Zhihong Wang (Journal of Cleaner Production, 2025)

Assessing thermal comfort for the elderly in historical districts and proposing adaptive urban design strategies: A case study in Zhenjiang, China - Yingnan Li; Yuhan Zhang; Yuedong Wang; Zipeng Song; Zhicheng Zhou; Lu Ding; Cen Chen; Xi Jin; Yuning Cheng (Landscape and Ecological Engineering, 2025)

Milk-derived small extracellular vesicles: a new perspective on dairy nutrition - Yuning Zhang; Yingying Lin; Jian He; Sijia Song; Yujia Luo; Yao Lu; Shuxing Chen; Qingyu Wang; Yixuan Li; Fazheng Ren; Huiyuan Guo (Critical Reviews in Food Science and Nutrition, 2024)

Synergistically enhanced heterogeneous activation of dissolved oxygen for aqueous carbamazepine degradation over S(III) coupled with siderite - Yuning Fang; Fei Wang; Hongze Fang; Zhaosheng Lei; Wei Song; Caixia Fu; Xing Du; Zhihong Wang; Zhiwei Zhao (Environmental Pollution, 2024)

On the Nearshore Significant Wave Height Inversion from Video Images Based on Deep Learning - Chao Xu; Rui Li; Wei Hu; Peng Ren; Yanchen Song; Haoqiang Tian; Zhiyong Wang; Weizhen Xu; Yuning Liu (Journal of Marine Science and Engineering, 2024)
Accurate observation of nearshore waves is crucial for coastal safety. In this study, the feasibility of extracting wave information from wave video images captured by shore-based cameras using deep learning methods was explored, focusing on inverting nearshore significant wave height (SWH) from instantaneous wave video images. The accuracy of deep learning models in classifying wind wave and swell wave images was investigated, providing reliable classification results for SWH inversion research. A classification network named ResNet-SW for wave types with improved ResNet was proposed. On this basis, the impact of instantaneous wave images, meteorological factors, and oceanographic factors on SWH inversion was evaluated, and an inversion network named Inversion-Net for SWH that integrates multiple factors was proposed. The inversion performance was significantly enhanced by the specialized models for wind wave and swell. Additionally, the inversion accuracy and stability were further enhanced by improving the loss function of Inversion-Net. Ultimately, time series inversion results were synthesized from the outputs of multiple models; the final inversion results yielded a mean absolute error of 0.04 m and a mean absolute percentage error of 8.52%. Despite certain limitations, this method can still serve as a useful alternative for wave observation.

A heat grid-driven method for generation of satellite observation tasks - Shilong Xu; Bingyu Song; Yingguo Chen; Jiawei Chen; Yuning Chen; Feiran Wang (Advances in Space Research, 2024)

Degradation of sulfamethazine in coastal aquaculture tailwater by Na2S2O4@iron-electrode electrooxidation combined with ceramic membrane process - Wei Song; Yuning Fang; Hongze Fang; Deming Gu; Xing Du; Sen Xu; Caixia Fu; Yu Zhou; Zhihong Wang (Environmental Pollution, 2024)

A New Prediction Model for Cutting Depth of Hard Rock Using High-Pressure Water Jets - Fuwei Liu; Yansen Wang; Xin Huang; Guoxuan Song; Yuning Wang (Rock Mechanics and Rock Engineering, 2024)

Knowledge-transfer based genetic programming algorithm for multi-objective dynamic agile earth observation satellite scheduling problem - Luona Wei; Ming Chen; Lining Xing; Qian Wan; Yanjie Song; Yuning Chen; Yingwu Chen (Swarm and Evolutionary Computation, 2024)

Variations in isoprenoid tetraether lipids through the water column of the Western Pacific Ocean: Implications for sedimentary TEX86 records - Jinqiang Guo; Zongyue Wang; Eric P. Achterberg; Huamao Yuan; Jinming Song; Yuning Wang; Xuegang Li; Liqin Duan; Baoxiao Qu (Geochimica et Cosmochimica Acta, 2024)

Changes in properties of human milk under different conditions of frozen storage - Kaibo Wang; Yanfeng Zhao; Sijia Song; Yingying Lin; Yujia Luo; Yafei Zhang; Yi Xue; Wusun Li; Yuning Zhang; Yao Lu; Heng Quan; Hao Zhang; et al. (Food Research International, 2024)

Two-dimensional graphene oxide/MXene lamellar membrane cross-linked by urea with adjustable interlayer spacing for efficient dye rejection and ion sieving - Dehao Yu; Liyue Sun; Yuning Zhang; Yu Song; Chenyu Jia; Yao Wang; Yanxin Wang; Matt J. Kipper; Jianguo Tang; Linjun Huang (Chemical Engineering Journal, 2024)

Sequence Stratigraphy, Sedimentology, and Reservoir Characteristics of the Middle Cretaceous Mishrif Formation, South Iraq - Leifu Zhang; Wenqi Zhang; Yong Li; Benbiao Song; Dawang Liu; Ya Deng; Jiacheng Xu; Yuning Wang (Journal of Marine Science and Engineering, 2023)
The Cenomanian–Early Turonian Mishrif Formation is a great contributor to oil production in Iraq. Integrating petrographic, mineralogical, and wireline logging data from 52 wells, this study provides an improved understanding of the sequence stratigraphy, depositional evolution, and reservoir characteristics of the Mishrif Formation in the Mesopotamian Basin, south Iraq. Five types of facies associations are classified: lagoon, shoal, rudist bioherm, shallow marine, and deep marine. Such a classification allows convenient differentiation and interpretation of wireline logs. A sequence stratigraphic framework including five third-order sequences (Mhf 1 to Mhf 5) for the Mishrif Formation is established mainly using wireline logging data of close-distance wells, with the aid of cores and thin sections. Two end-member depositional evolution stages are recognized, from clinoform-like progradational shoal complexes in Mhf 1 within a shallow marine environment, to tidal channels in Mhf 2–3 within a lagoon environment. For Mhf 4–5, abrupt changes in facies associations from north to south indicate the development of an intra-shelf basin where organic-rich mudstones directly overlie the shallow marine grainstone shoals and lagoonal wackestones. Reservoir characteristics and compartmentalization are directly controlled by the sequence stratigraphic framework. Sequence boundaries are featured by wackestones and mudstones overprinted by cementation; they are regionally correlatable and work as regional barriers. Shoal complexes in Mhf 1 and tidal channels in Mhf 2–3 are the main reservoir units. Mudstones and wackestones are intra-reservoir baffles and become more frequently developed towards the south, reflecting the increasing water depth towards south. The characterization of the tidal channels, clinoform-like shoals, and intrashelf basinal deposits in the current study could benefit later development of the Mishrif Formation.

Highly efficient base editing in rabbit by using near-PAMless engineered CRISPR/Cas9 variants - Zhongtian Zhang; Xinyu Wu; Jie Yang; Xin Liu; Ruonan Liu; Yuning Song (Science China Life Sciences, 2023)

Single and combined toxicity assessment of primary or UV-aged microplastics and adsorbed organic pollutants on microalga Chlorella pyrenoidosa - Wei Song; Caixia Fu; Yuning Fang; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Kalpana Bhatt; Lu Liu; Ningjie Wang; Fang Liu; Shunni Zhu (Environmental Pollution, 2023)

The self-association properties of partially dephosphorylated bovine beta-casein - Sijia Song; Yingying Lin; Yuning Zhang; Yujia Luo; Huiyuan Guo (Food Hydrocolloids, 2023)

Efficient and high-fidelity base editor with expanded PAM compatibility for cytidine dinucleotide - Zhiquan Liu; Siyu Chen; Yingqi Jia; Huanhuan Shan; Mao Chen; Yuning Song; Liangxue Lai; Zhanjun Li (Science China Life Sciences, 2021)

Linking Oceanic Tsunamis and Geodetic Gravity Changes of Large Earthquakes - Yuning Fu; Y. Tony Song; Richard S. Gross (Pure and Applied Geophysics, 2017)

Genomic imprinting analysis of Igf2/H19 in porcine cloned fetuses using parthenogenetic somatic cells as nuclear donors - Dongxu Wang; Yuning Song; Yongye Huang; Feifei Duan; Qinyan Lv; Hongsheng Ouyang; Liangxue Lai; Zhanjun Li (Biotechnology Letters, 2014)

Antigenic and genetic characterization of a European avian-like H1N1 swine influenza virus from a boy in China in 2011 - Xian Qi; Lunbiao Cui; Yongjun Jiao; Yuning Pan; Xihan Li; Rongqiang Zu; Xiang Huo; Bin Wu; Fengyang Tang; Yongchun Song; Minghao Zhou; Hua Wang; et al. (Archives of Virology, 2013)